2018
DOI: 10.1148/rg.2018170148
|View full text |Cite
|
Sign up to set email alerts
|

CT Findings of Acute Small-Bowel Entities

Abstract: Although a broad spectrum of entities can induce acute pathologic changes in the small bowel, there are relatively few imaging features that are characteristic of a specific diagnosis on the basis of CT findings. Specific clinical information, including time course and onset of disease, patient risk factors, and any recent pharmacologic or radiation therapy, is often instrumental in refining the differential diagnosis. A wide spectrum of disorders is reviewed in this article; however, given the breadth of diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Radiological methods play an important role in the diagnosis of jejunal perforation in the absence of specific clinical symptoms. Lawson et al suggest that era "trauma scan" leads to reduction missing body injuries, but the bowel injuries are still the most commonly missed and the key to success in treatment is clinical doubt about intestinal trauma in severe trauma patients [12]. Matsushima and colleges analyzed 7,875 blunt trauma patients, they found blunt hollow viscus and mesenteric injury (BHVMI) in 67 (0.8%) patients who were divided in two groups: non-ischemic-BHVMI (perforation, laceration, and hematoma without devascularization) and ischemic-BHVMI (devascularization confirmed at laparotomy) [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological methods play an important role in the diagnosis of jejunal perforation in the absence of specific clinical symptoms. Lawson et al suggest that era "trauma scan" leads to reduction missing body injuries, but the bowel injuries are still the most commonly missed and the key to success in treatment is clinical doubt about intestinal trauma in severe trauma patients [12]. Matsushima and colleges analyzed 7,875 blunt trauma patients, they found blunt hollow viscus and mesenteric injury (BHVMI) in 67 (0.8%) patients who were divided in two groups: non-ischemic-BHVMI (perforation, laceration, and hematoma without devascularization) and ischemic-BHVMI (devascularization confirmed at laparotomy) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Matsushima and colleges analyzed 7,875 blunt trauma patients, they found blunt hollow viscus and mesenteric injury (BHVMI) in 67 (0.8%) patients who were divided in two groups: non-ischemic-BHVMI (perforation, laceration, and hematoma without devascularization) and ischemic-BHVMI (devascularization confirmed at laparotomy) [13]. Authors found that even using an advanced imaging technique, the diagnosis of I-BHVMI can be delayed, with significant negative impact on patient outcome [12].…”
Section: Discussionmentioning
confidence: 99%
“…Generalized vasospasm may be obvious as narrowing of IVC, aorta and mesenteric vessels resulting in decreased enhancement of affected bowel segments and occasionally other organs (liver, spleen and pancreas) [74]. Bowel wall thickness ranges from unchanged in earliest stages to markedly thinned in an advanced stage [40,74].…”
Section: Non-occlusivementioning
confidence: 99%
“…Mixed arterial and venous ischemia are also infrequently seen in association with other conditions including trauma, chemotherapy, irradiation, drug induced, corrosive injury, lead poisoning, iatrogenic, etc. [74] (Figs. 22,23,24,25,26,27,28).…”
Section: Mixed (Strangulation) and Other Miscellaneous Causesmentioning
confidence: 99%
“…In addition, CT signs associated with hypotension complex can be important indicators of systemic hypotension, which may facilitate the differential diagnosis. Shock bowel has a mortality rate of up to 70% [23][24][25][26][28][29][30][31].…”
Section: Bowel Hypoperfusion (Shock Bowel)mentioning
confidence: 99%